The Impact of Social Media Marketing and E-Wom on Purchase Intention: A Study in the Local Shoe Industry - Salsabila, Anzani Zahra; Andrean, Timothy; Gladiola, Yolanda; Setiowati , Rini (International Journal Labs, 2025)
The rapid growth of digital platforms has transformed how consumers interact with brands, particularly in emerging markets like Indonesia where local industries face intense competition with global players. Among the various tools available, social media marketing and electronic word-of-mouth (e-WOM) are increasingly recognized as crucial drivers of consumer engagement, brand awareness, and purchase intention. However, studies that integrate both variables in a single framework, particularly in the context of the Indonesian local shoe industry, remain limited. This research aims to fill that gap by examining the combined effects of social media marketing and e-WOM on purchase intention, mediated by brand awareness and customer trust. A quantitative approach was employed by distributing structured questionnaires to 200 respondents in the JABODETABEK region who had not previously purchased local shoe brands. The results indicate that most of the proposed hypotheses are supported, with the exception that e-WOM exhibits a negative and significant influence on brand awareness. These findings suggest that not all digital interactions contribute positively to brand equity, highlighting the risk of negative online reviews or misinformation. Theoretically, this study enriches the literature on digital consumer behavior in emerging markets by providing evidence of the nuanced effects of e-WOM. Practically, it offers valuable implications for local shoe manufacturers and marketers in designing effective strategies that enhance customer trust, strengthen brand positioning, and ultimately increase purchase intention. Future research can extend this model by incorporating other moderating variables such as cultural values, product involvement, or customer experience.